Analisis Zink Pirition dalam Sampo Anti Ketombe secara Kromatografi Cair Kinerja Tinggi untuk Mendukung Pengawasan Pre-Market dan Post-Market - Zahara, Zahara; Kurniawati, Farida; Lusianti, Erita (Eruditio : Indonesia Journal of Food and Drug Safety, 2024)
ZnPtO is widely used as an active substance in anti-dandruff shampoo. Instead of describing its benefits, many articles have reported that ZnPtO can harm the environment and human health. Through the Food and Drugs Administration, Indonesia has been regulated to have a maximum limit of 2.0% for rinse-off hair products. The research aims to develop an accurate and reliable method to determine product ZnPtO level. ZnPtO was analyzed using High-Performance Liquid Chromatography (HPLC) with Photo Diode Array (PDA) at a wavelength of 257.9 nm. This research used a C18 column with dimensions of 250 x 4.6 nm and five μm in particle size. The mobile phase consisted of acetonitrile and a mixture of potassium dihydrogen phosphate solution and disodium EDTA at pH 4.0 (30:70). Column temperature was maintained at 40oC at a 1.0 ml/min flow rate.  The results showed that ZnPtO was detected at a retention time of 7 minutes. The method's correlation coefficient and residual deviation were 0.999% and 0.65%, respectively. Method precision at 20, 100, and 160 μg/ml was 0.6694, 0.4511, and 0.4728%, respectively. Method accuracy at those levels was 98.3 to 100.9%. All validation parameters have fulfilled the qualification. ZnPtO levels contained in anti-dandruff shampoos were 0.0081%, 0.0040%, and 0.016%, respectively. The developed method has proven selective, accurate, and reliable. It can control the quality and safety of anti-dandruff shampoo due to pre-market and post-market surveillance.